Galts "Dickson's Hill": The Evolution of a Late-Victorian Neighbourhood in an Ontarian Town - Hagopian, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1999)
Previous research has shown that the economic growth and urban population increases which occurred in the 1880s prompted the development of many new residential neighbourhoods in central Canadian municipalities. Much of this housing was of superior quality, to meet the needs of the growing middle and upper classes, who began to segregate themselves in affluent enclaves within cities. These neighbourhoods evolved slowly, reflecting the small scale of the processes of land subdivision and housing construction which then existed. These processes, however, were in a state of transition, and by the early 20th century, housing provision had become more professional and large scale.The present research uses the case of Dickson's Hill to explore how these and other events unfolded in a Late Victorian neighbourhood in a small Ontarian town. The social segregation which occurred here was not extreme, as the rich and poor lived on opposite sides of the same neighbourhood. The basic street pattern and most of the subdividing of land was done by one person — Florence Dickson — but many builders and tradesmen were involved in the provision of housing. There was much variation in house styles, even on the same block, since individual lot owners contracted for the construction of their homes, and since the pace of development was so slow that the popularity of certain architectural styles had changed. This variety, together with a number of planning decisions, explains in part the character and charm exuded by the neighbourhood.